Strategic state-building points in George Y. Shevelov’s historiosophical stance. - Karunyk, Kateryna (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The purpose. On the basis of unknown and rare George Y. Shevelov’s newspaper publications of the 1940s-1950s the paper intends to trace his historiosophical stance and to single out his strategic points for the Ukrainian scholars concerning re-establishing and strengthening Ukraine as an independent state.Approaches. The paper relays on a set of interdisciplinary approaches which involve elements of historiographical research, of political philosophy, of cultural studies, of text and discourse analysis, and some comparative approaches as well.Research achievements. The insight into George Y. Shevelov’s publications in the scope of political philosophy substantially complement up-to-date image of the author as a political thinker. These essays of his were not just a minute reaction to the current events or discourse, but they rather offer sustainable ideological vision of historical and psychological prerequisites of the Ukrainian nation-building process, albeit the Ukrainians themselves, baring natural state-building potential, for centuries found it fascinating to construct the alien empire. The essayist reveals the reasons of such psychological drawbacks of the people as provincialism or treachery, at the same time he uplifts their “eagerness to build empire” as well as their cultural and intellectual European-mindedness. Shevelov treats the Ukrainian nationalism neither in a sense of militant activity, nor as political agenda, but rather in a paradigm of multisided cultural experience due to which the people, having felt consciously their unity, matured finally into the distinct organism.Conclusions. The insight into this set of Shevelov’s publications allows to sum up and complete the author’s historiosophical stance of the Ukrainian nation-building process. In his writings the tribute was paid to the Western philosophers together with the Ukrainian intellectuals of the 20th century whose ideas Shevelov synthesized in his special way. He postulated continuing, interrupted history, which shows the people’s fostering after numerous border changes – the people which matures into a nation, a kind of unitas multiplex, with conscious will to establish and struggle for their own state. Besides, the author gives a set of strategic tasks to the Ukrainian scholars who could focus on Russian and East European studies and to politicians who can initiate and manage the anti-Russian coalition preventing any aggression from Moscow.